TGFβ Signaling-mediated MicroRNA Regulation in Vascular Smooth Muscle Cells - Kim, Sunghwan (J Lifestyle Med, 2013)
The discovery of small noncoding microRNAs (miRNAs) increases the complexity of gene expression regulatory mechanisms. The basic mechanism of miRNA biogenesis and regulatory functions of target genes have been widely elucidated. Recently, it has been recognized that regulation of each step of miRNA biogenesis is critical for generating functional miRNAs. Interestingly, cell signaling pathways, including the transforming growth factor β (TGFβ) signaling pathway, have been found to modulate miRNA biosynthesis. TGFβ signaling regulates expression of several miRNAs that are implicated in the development and homeostasis of vascular smooth muscle cells (VSMCs). This review describes recent understanding of the transcriptional and post-transcriptional regulation of miRNA expression by TGF β signaling in VSMCs.